HUKUM PERJANJIAN AKAN JUAL BELI SEBIDANG TANAH DENGAN PANJER SESUDAH BERLAKUNYA UU NO. 5 TAHUN 1960 DI SAMARINDA - Frederik Melawen (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTThat the validity will be buying and selling that have been expressed by the judges by taking the example of a civil case No. 30 / Pdt.G / 2002 / PN.Samarinda still premateur. But already a reality in a verdict. For the defeated party should or less satisfied with the decision, exercised its right to take legal actions which appeals during the court's decision does not have binding legal force (inkracht Van Gewisjde), commencing after 14 (fourteen) days verdict was notified.If passed within 14 (fourteen) days after the decision is given to the defeated party but not used his rights, court decisions should be deemed to have has permanent legal force (inkracht Van Gewisjde).That the legal power purchase agreements in spite of the principle of freedom of contract as stated in article 1338 of the Civil Code can not be said to have the force of law. But has become a reality, the legal power purchase agreement as in this case to be considered legal power purchase agreement depends on the validity of which has been decided by the courts.The reality, as has been decided by the court that turned out to be an agreement of sale were corroborated and declared legally valid. Therefore, inevitably purchase agreement between the Defendant I to Defendant II is void.